Increased quadriceps intermuscular adipose tissue in chronic liver disease is associated with an altered muscle transcriptome compared with healthy age matched controls - J. I. Quinlan; T. Nicholson; C. Bell; A. Dhaliwal; F. R. Williams; S. L. Allen; S. Choudhary; A. V. Rowlands; A. M. Elsharkawy; M. J. Armstrong; C. A. Greig; J. M. Lord; et al. (GeroScience, 2025)
Muscle fat infiltration (i.e., myosteatosis) is an important index of muscle health and pathology in disease states, such as chronic liver disease (CLD). However, it is unknown whether myosteatosis differs due to anatomical location. Further, the mechanistic implications of divergent intermuscular adipose tissue (IMAT) deposition remain unknown in patients with CLD. Thirty-three patients with CLD (55.0 ± 10.5 years) and 17 healthy controls (HC) (49.6 ± 15.4 years) were recruited. Quadriceps IMAT was estimated between 20 and 80% of muscle length and psoas IMAT at L3 via MRI. Body composition, muscle strength, and habitual activity were assessed. Fasted vastus lateralis muscle biopsies were collected and subjected to RNA sequencing analysis. ClinicalTrials.gov identifier: NCT04734496. IMAT was greater in CLD compared with HC in both quadriceps and psoas ( P < 0.0001). Quadriceps IMAT positively correlated with BMI ( r = 0.62), body fat ( r = 0.65), age ( r = 0.36), and negatively correlated with maximal knee extensor strength ( r = −0.45) and habitual physical activity ( r = −0.50) in CLD and HC. One hundred sixty-nine differentially expressed genes (DEGs) were identified in low IMAT CLD vs. HC, and 178 DEGs were identified in high IMAT CLD vs. HC. CLD patients with high and low IMAT exhibited defined expression profiles, with only 39 DEGs (representing 12.7%) in common. Pathway analysis of DEGs revealed enrichment of atrophic and pro-inflammatory pathways in the high IMAT group. IMAT is greater in patients with CLD compared to HC, irrespective of anatomical location, and is associated with reductions in muscle function and may be exacerbated by physical inactivity. IMAT appears to alter the muscle transcriptome in COLD, potentially exacerbating muscle loss. Graphical Abstract

P19-19 Application of InSight™ human 3D MASLD/MASH spheroid models for DILI assessment of compounds - P. Vonschallen; A. Pawlowska; B. Filippi; L. Fäs; T. Hofstetter; J. Zvick; J. Glaus; A.B. Breen; F. Verdeguer; R. Kostadinova (Toxicology Letters, 2025)

Tundra Plant Canopies Gradually Close Over Three Decades While Cryptogams Persist - Katlyn R. Betway‐May; William A. Gould; Sarah C. Elmendorf; Jeremy L. May; Robert D. Hollister; Steven F. Oberbauer; Amy Breen; Benjamin J. Crain; Ana Maria Sanchez Cuervo; Marilyn D. Walker; Donald A. Walker (Global Change Biology, 2025)
Global climate change phenomena are amplified in Arctic regions, driving rapid changes in the biota. Here, we examine changes in plant community structure over more than 30 years at two sites in arctic Alaska, USA, Imnavait Creek and Toolik Lake, to understand long‐term trends in tundra response to changing climate. Vegetation cover was sampled every 4–7 years on permanent 1 m 2 plots spanning a 1 km 2 grid using a point‐frame. The vascular plant canopies progressively closed at both locations. Canopy cover, defined here as an encounter of a vascular plant above the ground surface, increased from 63% to 91% at Imnavait Creek and from 63% to 89% at Toolik Lake. Both sites showed steady increases in maximum canopy height, increasing by approximately 50% (8 cm). While cover and height increased to some extent for all vascular plant growth forms, deciduous shrubs and graminoids changed the most. For example, at Imnavait Creek the cover of graminoids more than tripled (particularly in wet meadow plots), increasing by 237%. At Toolik Lake the cover of deciduous shrubs more than doubled (particularly in moist acidic plots), increasing by 145%. Despite the steady closing of the plant canopy, cryptogams (lichens and mosses) persisted; in fact, the cover of lichens increased. These results call into question the dominant dogma that cryptogams will decline with increases in vascular plant abundance and demonstrate the resilience of these understory plants. In addition to overall cover, the diversity of vascular plants increased at one site (Imnavait Creek). In contrast to much of the Arctic, summer air temperatures in the Toolik Lake region have not significantly increased over the 30+ year sampling period; however, winter temperatures increased substantially. Changes in vegetation community structure at Imnavait Creek and Toolik Lake are likely the result of winter warming.

Knowledge brokers at the interface of environmental science and policy: A review of knowledge and research needs - C. Cvitanovic; DB Karcher; J. Breen; N. Badullovich; P. Cairney; R. Dalla Pozza; J. Duggan; S. Hoffmann; R. Kelly; AM Meadow; S. Posner (Environmental Science & Policy, 2025)

Bioeconomic and sustainability performance of dairy-beef steer and heifer production systems differing in stocking rate - M. Kearney; E.G. O'Riordan; M. McGee; J. Breen; R. Dunne; P. French; P. Crosson (Livestock Science, 2024)

Effect of Octamer-Binding Transcription Factor 4 Overexpression on the Neural Induction of Human Dental Pulp Stem Cells - Maria R. Gancheva; Karlea Kremer; James Breen; Agnes Arthur; Anne Hamilton-Bruce; Paul Thomas; Stan Gronthos; Simon Koblar (Stem Cell Reviews and Reports, 2024)
Stem cell-based therapy is a potential alternative strategy for brain repair, with neural stem cells (NSC) presenting as the most promising candidates. Obtaining sufficient quantities of NSC for clinical applications is challenging, therefore alternative cell types, such as neural crest-derived dental pulp stem cells (DPSC), may be considered. Human DPSC possess neurogenic potential, exerting positive effects in the damaged brain through paracrine effects. However, a method for conversion of DPSC into NSC has yet to be developed. Here, overexpression of octamer-binding transcription factor 4 (OCT4) in combination with neural inductive conditions was used to reprogram human DPSC along the neural lineage. The reprogrammed DPSC demonstrated a neuronal-like phenotype, with increased expression levels of neural markers, limited capacity for sphere formation, and enhanced neuronal but not glial differentiation. Transcriptomic analysis further highlighted the expression of genes associated with neural and neuronal functions. In vivo analysis using a developmental avian model showed that implanted DPSC survived in the developing central nervous system and respond to endogenous signals, displaying neuronal phenotypes. Therefore, OCT4 enhances the neural potential of DPSC, which exhibited characteristics aligning with neuronal progenitors. This method can be used to standardise DPSC neural induction and provide an alternative source of neural cell types. Graphical Abstract

S15-01: Modelling kinetics and dynamics of chemicals at the US-EPA using the httk open-source platform - J. Wambaugh; S. Davidson-Fritz; A. Meade; M. Breen; R. Sayre; T. Wall; E. Kenyon; M. Evans; B. Wetmore; C. Ring (Toxicology Letters, 2023)

A holistic and comprehensive data approach validates the distribution of the critically endangered flapper skate ( Dipturus intermedius ) - Amy Garbett; Sophie L. Loca; Thomas Barreau; Manuel Biscoito; Caroline Bradley; Joe Breen; Maurice Clarke; Jim R. Ellis; Andrew M. Griffiths; Gary Hannon; Klara Jakobsdóttir; Claudia Junge; et al. (Journal of Fish Biology, 2023)
Morphological similarities between skates of the genus Dipturus in the north‐eastern Atlantic and Mediterranean have resulted in longstanding confusion, misidentification and misreporting. Current evidence indicates that the common skate is best explained as two species, the flapper skate ( Dipturus intermedius ) and the common blue skate ( D. batis ). However, some management and conservation initiatives developed prior to the separation continue to refer to common skate (as ‘ D. batis’ ). This taxonomic uncertainty can lead to errors in estimating population viability, distribution range, and impact on fisheries management and conservation status. Here, we demonstrate how a concerted taxonomic approach, using molecular data and a combination of survey, angler and fisheries data, in addition to expert witness statements, can be used to build a higher resolution picture of the current distribution of D. intermedius . Collated data indicate that flapper skate has a more constrained distribution compared to the perceived distribution of the ‘common skate’, with most observations recorded from Norway and the western and northern seaboards of Ireland and Scotland, with occasional specimens from Portugal and the Azores. Overall, the revised spatial distribution of D. intermedius has significantly reduced the extant range of the species, indicating a possibly fragmented distribution range.

Remission of insomnia in older adults treated with cognitive behavioral therapy for insomnia (CBT-I) reduces p16INK4a gene expression in peripheral blood: secondary outcome analysis from a randomized clinical trial - Judith E. Carroll; Richard Olmstead; Steve W. Cole; Elizabeth C. Breen; Jesusa M. Arevalo; Michael R. Irwin (GeroScience, 2023)
Late life insomnia may increase risk for accelerated biological aging. Intervening to treat insomnia may provide protection from biological aging by reducing the prevalence of senescent cells in the immune system, as indicated by gene expression of a marker of cellular senescence, p16 INK4a . In the present study, we determine whether treatment of insomnia in older adults with cognitive behavioral therapy for insomnia (CBT-I) would reduce p16 INK4a gene expression in peripheral blood mononuclear cells (PBMC), compared to a sleep education therapy (SET), an active comparator condition. Secondly, we investigate the relationship between sustained insomnia remission and reduced expression of p16 INK4a . Participants 60 + years old with insomnia were enrolled in a randomized controlled trial and assigned to CBT-I or SET. Analyses of 231 older adults (CBT-I = 119; SET = 112) examine baseline, post (2 months), and 24 months gene expression of p16 INK4a . Compared to baseline, expression of p16 INK4a increased in the SET group over 24 months ( P = 0.03), but showed no change in the CBT-I group. Those who received CBT-I and experienced sustained remission of insomnia had a significant decline in p16 INK4a expression by 24 months compared to baseline ( P = 0.02). Individuals not sustaining remission of insomnia exhibited overall increase expression of p16 INK4a by 24 months ( P = 0.03). In older adults with insomnia, p16 INK4a increases over 24 months, while CBT-I treatment of insomnia mitigates the increase in p16 INK4a . Further, sustained remission of insomnia using CBT-I leads to a decrease in p16 INK4a . These results suggest that behavioral interventions that are effective at treating insomnia might reduce the population of senescent cells in circulating blood.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Investigating the contribution of white matter hyperintensities and cortical thickness to empathy in neurodegenerative and cerebrovascular diseases - Miracle Ozzoude; Brenda Varriano; Derek Beaton; Joel Ramirez; Melissa F. Holmes; Christopher J. M. Scott; Fuqiang Gao; Kelly M. Sunderland; Paula McLaughlin; Jennifer Rabin; Maged Goubran; Donna Kwan; et al. (GeroScience, 2022)

Atlantic mackerel ( Scomber scombrus ) change skin colour in response to crowding stress - Guro M. Tveit; Neil Anders; Morten S. Bondø; John R. Mathiassen; Mike Breen (Journal of Fish Biology, 2022)
Wild capture can be stressful for fish. Stress has the potential to induce mortality in released unwanted catches or negative flesh quality consequences in retained ones. Such effects compromise sustainable natural resource management and industry profitability. Mitigating stress during capture is therefore desirable. Biological indicators of stress can objectively inform fishers as to the functional welfare status of catches during fishing operations. If they are to be of practical use in mitigating stress during wild capture events, such indicators must be quantifiable, respond rapidly, reflect the level of induced stress and be easily observable. Atlantic mackerel ( Scomber scombrus ) are extensively targeted by purse seine fisheries in European waters but are particularly vulnerable to stress. Excessive crowding in the net is thought to be the principal stress mechanism. There is therefore a need to develop indicators of crowding stress for this species so that catch welfare can be improved. Here, we demonstrate that S. scombrus exhibit a skin colour change from predominately green to predominately blue when exposed to crowding stress. In sea cage trials, we induced various degrees of stress in groups of wild‐caught S. scombrus by manipulating crowding density and its duration. Skin colour was quantified in air using digital photography. The colour change occurred rapidly (within the typical duration of crowding events in the fishery), and its magnitude was correlated to the severity and duration of crowding. Bluer fish were also associated with higher levels of plasma lactate. No appreciable colour change was observed in uncrowded (control) groups during the treatment period. Nonetheless, unstressed S. scombrus did turn blue S. scombrus and could therefore be used to improve welfare during wild capture fishing.

Stakeholders and social networks identify potential roles of communities in sustainable management of invasive species - Harriet A. Omondiagbe; David R. Towns; Jay K. Wood; Barbara Bollard-Breen (Biological Invasions, 2017)

Thermokarst rates intensify due to climate change and forest fragmentation in an Alaskan boreal forest lowland - Mark J. Lara; Hélène Genet; Anthony D. McGuire; Eugénie S. Euskirchen; Yujin Zhang; Dana R. N. Brown; Mark T. Jorgenson; Vladimir Romanovsky; Amy Breen; William R. Bolton (Global Change Biology, 2016)
Lowland boreal forest ecosystems in Alaska are dominated by wetlands comprised of a complex mosaic of fens, collapse‐scar bogs, low shrub/scrub, and forests growing on elevated ice‐rich permafrost soils. Thermokarst has affected the lowlands of the Tanana Flats in central Alaska for centuries, as thawing permafrost collapses forests that transition to wetlands. Located within the discontinuous permafrost zone, this region has significantly warmed over the past half‐century, and much of these carbon‐rich permafrost soils are now within ~0.5 °C of thawing. Increased permafrost thaw in lowland boreal forests in response to warming may have consequences for the climate system. This study evaluates the trajectories and potential drivers of 60 years of forest change in a landscape subjected to permafrost thaw in unburned dominant forest types (paper birch and black spruce) associated with location on elevated permafrost plateau and across multiple time periods (1949, 1978, 1986, 1998, and 2009) using historical and contemporary aerial and satellite images for change detection. We developed (i) a deterministic statistical model to evaluate the potential climatic controls on forest change using gradient boosting and regression tree analysis, and (ii) a 30 × 30 m land cover map of the Tanana Flats to estimate the potential landscape‐level losses of forest area due to thermokarst from 1949 to 2009. Over the 60‐year period, we observed a nonlinear loss of birch forests and a relatively continuous gain of spruce forest associated with thermokarst and forest succession, while gradient boosting/regression tree models identify precipitation and forest fragmentation as the primary factors controlling birch and spruce forest change, respectively. Between 1950 and 2009, landscape‐level analysis estimates a transition of ~15 km² or ~7% of birch forests to wetlands, where the greatest change followed warm periods. This work highlights that the vulnerability and resilience of lowland ice‐rich permafrost ecosystems to climate changes depend on forest type.

A novel canine kidney cell line model for the evaluation of neoplastic development: karyotype evolution associated with spontaneous immortalization and tumorigenicity - R. Omeir; R. Thomas; B. Teferedegne; C. Williams; G. Foseh; J. Macauley; L. Brinster; J. Beren; K. Peden; M. Breen; A. M. Lewis (Chromosome Research, 2015)

US trends in survival disparities among adolescents and young adults with non-Hodgkin lymphoma - Erin E. Kent; Nancy Breen; Denise R. Lewis; Janet S. de Moor; Ashley Wilder Smith; Nita L. Seibel (Cancer Causes & Control, 2015)

Application of an unmanned aerial vehicle in spatial mapping of terrestrial biology and human disturbance in the McMurdo Dry Valleys, East Antarctica - Barbara Bollard-Breen; John D. Brooks; Matthew R. L. Jones; John Robertson; Sonja Betschart; Olivier Kung; S. Craig Cary; Charles K. Lee; Stephen B. Pointing (Polar Biology, 2015)

Genetic risk score analysis indicates migraine with and without comorbid depression are genetically different disorders - Lannie Ligthart; Jouke-Jan Hottenga; Cathryn M. Lewis; Anne E. Farmer; Ian W. Craig; Gerome Breen; Gonneke Willemsen; Jacqueline M. Vink; Christel M. Middeldorp; Enda M. Byrne; Andrew C. Heath; Pamela A. F. Madden; et al. (Human Genetics, 2014)

The association between pro-inflammatory cytokines, regional cerebral metabolism, and cognitive complaints following adjuvant chemotherapy for breast cancer - K. L. Pomykala; P. A. Ganz; J. E. Bower; L. Kwan; S. A. Castellon; S. Mallam; I. Cheng; R. Ahn; E. C. Breen; M. R. Irwin; D. H. S. Silverman (Brain Imaging and Behavior, 2013)

A multiple resistance locus on chromosome arm 3BS in wheat confers resistance to stem rust (Sr2), leaf rust (Lr27) and powdery mildew - R. Mago; L. Tabe; R. A. McIntosh; Z. Pretorius; R. Kota; E. Paux; T. Wicker; J. Breen; E. S. Lagudah; J. G. Ellis; W. Spielmeyer (Theoretical and Applied Genetics, 2011)

Erratum to: An accurate DNA marker assay for stem rust resistance gene Sr2 in wheat - R. Mago; H. Simkova; G. Brown-Guedira; S. Dreisigacker; J. Breen; Y. Jin; R. Singh; R. Appels; E. S. Lagudah; J. Ellis; J. Dolezel; W. Spielmeyer (Theoretical and Applied Genetics, 2011)

An accurate DNA marker assay for stem rust resistance gene Sr2 in wheat - R. Mago; G. Brown-Guedira; S. Dreisigacker; J. Breen; Y. Jin; R. Singh; R. Appels; E. S. Lagudah; J. Ellis; W. Spielmeyer (Theoretical and Applied Genetics, 2011)

Are lobster fisheries being managed effectively? Examples from New Zealand and Nova Scotia - R. J. MILLER; P. A. BREEN (Fisheries Management and Ecology, 2010)
Based on performance, management of the New Zealand and Nova Scotia lobster fisheries can be considered successful, but management can be improved by clearer statements of objectives, more efficient mechanics of governance and quicker response to changes in stocks or fisheries. Principal tactics for lobster fishery management are individual transferable quotas and input controls in New Zealand and Nova Scotia respectively. Decision rules were considered important in both approaches and examples are provided of underperforming fisheries in the absence of decision rules. In Nova Scotia, strong fishers’ organisations and fishery scientists were effective agents for change, whereas fisher advisory committees operating by consensus were not. In New Zealand, the quota management system provided strong incentives for fishers to become involved in responsible management, to take longer‐term views of their resource and to take major management action on their own.

PAVA: physiological and anatomical visual analytics for mapping of tissue-specific concentration and time-course data - Michael-Rock Goldsmith; Thomas R. Transue; Daniel T. Chang; Rogelio Tornero-Velez; Michael S. Breen; Curtis C. Dary (Journal of Pharmacokinetics and Pharmacodynamics, 2010)

Influence of genetic background on tumor karyotypes: Evidence for breed-associated cytogenetic aberrations in canine appendicular osteosarcoma - Rachael Thomas; Huixia J. Wang; Pei-Chien Tsai; Cordelia F. Langford; Susan P. Fosmire; Cristan M. Jubala; David M. Getzy; Gary R. Cutter; Jaime F. Modiano; Matthew Breen (Chromosome Research, 2009)

A voluntary reduction in the commercial catch of rock lobster (Jasus edwardsii) in a New Zealand fishery - Paul A. Breen; Daryl R. Sykes; Paul J. Starr; Susan Kim; Vivian Haist (New Zealand Journal of Marine and Freshwater Research, 2009)
We describe the development and application of a management procedure (decision rule) that resulted in a voluntary reduction in the commercial catch of spiny rock lobster ( Jasus edwardsii ) in the lower east coast of North Island of New Zealand. The management procedure was developed from an accepted assessment of the CRA 4 (Wellington‐Hawke's Bay) fishery, which used an integrated length‐based assessment model fitted to commercial fishery catch‐per‐unit‐effort (CPUE) biomass indices, commercial length‐frequency data, and tag‐recapture data. The assessment model had been Bayesian, and used the joint posterior distribution of parameters to predict the effect of 384 alternative harvest control rules on the future size of the CRA 4 stock. The harvest control rules all used CPUE as their input, and generated annual changes in catch, which were then simulated by the population dynamics of the operating model. Uncertainty was added to evaluations through observation error, added to the simulated CPUE observations, and stochastic serial auto‐correlation variation in recruitment. We describe how this management procedure was used to effect a voluntary reduction in catch to address the problem of a rapidly declining population.

Electronic tags reveal behaviour of captured and discarded fish - F. C. Neat; M. Breen; R. M. Cook; I. M. Gibb; P. J. Wright (Journal of Fish Biology, 2009)
Internally implanted data storage tags (DST) recording hydrostatic pressure (depth) and temperature in Atlantic cod Gadus morhua were used to track the behaviour of nine individuals during fishing operations. Gadus morhua showed identifiable and characteristic behavioural responses to different capture processes. In a unique observation, one fish survived being discarded and upon return to the seabed exhibited a cessation of activity comparable to observations on stressed fish under laboratory conditions.

Watershed Nitrogen and Mercury Geochemical Fluxes Integrate Landscape Factors in Long-term Research Watersheds at Acadia National Park, Maine, USA - J. S. Kahl; S. J. Nelson; I. Fernandez; T. Haines; S. Norton; G. B. Wiersma; G. Jacobson; A. Amirbahman; K. Johnson; M. Schauffler; L. Rustad; K. Tonnessen; et al. (Environmental Monitoring and Assessment, 2007)

The search for a marsupial XIC reveals a break with vertebrate synteny - Lance S. Davidow; Matthew Breen; Shannon E. Duke; Paul B. Samollow; John R. McCarrey; Jeannie T. Lee (Chromosome Research, 2007)

Estimated Ultraviolet Radiation Doses in Wetlands in Six National Parks - Stephen A. Diamond; Peter C. Trenham; Michael J. Adams; Blake R. Hossack; Roland A. Knapp; Stacey L. Stark; David Bradford; P. Stephen Corn; Ken Czarnowski; Paul D. Brooks; Dan Fagre; Bob Breen; et al. (Ecosystems, 2005)

A new framework marker-based linkage map and SDPs for the Rat HXB/BXH strain set - Martin Jirout; Drahomra Krenov; Vladimr Kren; Laura Breen; Michal Pravenec; Nicholas J. Schork; Morton P. Printz (Mammalian Genome, 2003)

Bymixer provides on-line calibration of measurement of CO2 volume exhaled per breath - Peter H. Breen; Eugene R. Serina (Annals of Biomedical Engineering, 1997)